2020
DOI: 10.1186/s13071-020-04186-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of exosome-like vesicles derived from Taenia pisiformis cysticercus and their immunoregulatory role on macrophages

Abstract: Background: Taenia pisiformis is one of the most common intestinal parasites in canines, and leads to serious economic losses in the rabbit breeding industry. Exosome-like vesicles from parasites play crucial roles in host-parasite interactions by transferring cargo from parasites to host cells and by modulating host immunological response through inducing production of host-derived cytokines. Nevertheless, the mechanism by which exosome-like vesicles from T. pisiformis cysticercus regulate the macrophage immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 57 publications
4
13
0
Order By: Relevance
“…Further, ITEM analysis indicated that the isolated vesicles contained two exosomal markers CD9 and CD63 ( Figure 1 B). The size distribution of the particles was shown to range predominantly from 50 nm to 200 nm in diameter ( Figure 1 C), consistent with our previous study [ 14 ]. Taken together, the TEM, ITEM and NTA analyses confirmed that exosome-like vesicles were successfully isolated from ESPs of T. pisiformis cysticercus.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Further, ITEM analysis indicated that the isolated vesicles contained two exosomal markers CD9 and CD63 ( Figure 1 B). The size distribution of the particles was shown to range predominantly from 50 nm to 200 nm in diameter ( Figure 1 C), consistent with our previous study [ 14 ]. Taken together, the TEM, ITEM and NTA analyses confirmed that exosome-like vesicles were successfully isolated from ESPs of T. pisiformis cysticercus.…”
Section: Resultssupporting
confidence: 91%
“…Culture media were refreshed after 12 h to remove contaminants from host components. The excretory/secretory products (ESPs) of T. pisiformis cysticerci were collected at 24 h and 48 h. Isolation of exosome-like vesicles was carried out from pooled ESPs as described in our previous study [ 14 ]. The size of isolated exosome-like vesicles was determined using a NanoSight LM10 instrument (Nanosight, Wiltshire, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of EVs, such as small RNA and/or protein profiles is available for some cestode species (Wang et al, 2020b). In E. granulosus, studies were carried out on EVs isolated from hydatid cyst fluid (HCF) directly from hosts with CE (Siles-Lucas et al, 2017; Zhou et al, 2019) and cultured protoscoleces (Nicolao et al, 2019), leading to the identification of highly immunogenic antigens, such as antigen 5, Antigen B, P29 and endophilin-1.…”
Section: Cestodesmentioning
confidence: 99%